Painting is Easier...Everywhere! - Dow Chemical Company (1951)
Color print advertisement for Dow Chemical. The advertisement features an illustrated "Santa's workshop" scene, where elves are painting a variety of children's toys. The accompanying text describes recent improvements in paint's "ease of application." This innovation is attributed to chemical products that Dow supplies to paint manufacturers, such as phenol, glycols, latexes and resins.
Keywords: Dow Chemical Company; Advertising; Chemical industry; Corporations; Painting; Santa Claus; Paint industry and trade; Christmas; Advertising, Industrial